Protective Effect of Aloe vera and Croton palanostigma against Acute Gastric Mucosa Injury Induced by Ethanol in Rats - Ayala Pío, Salomón (1999)
OBJECTIVE: The gastric protective abilities of Croton palanostigma (dragonis blood), Aloe vera, sucralfate, and antacid against acute ethanol-induced necrosis by means of a standard experimental model in rats, were compared. MATERIAL AND METHODS: A pretreatment with either saline solution; 0,8 mL/kg or 0,4 mL/kg C. palanostigma; 7,5 mL/kg or 3,2 mL/kg A. vera; 500 mg/kg sucralfate; or antacid was given to 56 fasted rats. Then we accomplished an intragastric administration of 2 mL of 100% ethanol one hour later. A gastrectomy was performed four hours later followed by a macroscopic and histologycal evaluation of the gastric lesions. RESULTS: C. palanostigma pretreatment resulted in a significant reduction of ethanol-induced gastric mucosa Protective effect of Croton palanostigma, Aloe vera, SUCRALFATE AND ANTACID AGAINST ACUTE ETHANOL-INDUCED GASTRIC MUCOSA necrosis. A. vera failed to show mucosal protection. Sucralfate showed a significant protective effect, while antacid exhibited a lesser protective effect. CONCLUSION: In the present study, C. palanostigma showed an important protective effect, being potentially useful as a therapeutic tool.